Relevansi Tafsir Marah Labid Imam Nawawi Al-Bantani Dalam Konteks Globalisasi dan Modernisasi - Heri Iswandi (Kilau Publishing, 2026)
This This study examines the relevance of Tafsir Marah Labid by Imam Nawawi Al-Bantani in responding to the challenges of globalization and modernization that affect the lives of contemporary Muslims. As one of the prominent scholars from the Indonesian archipelago with a universal outlook, Imam Nawawi Al-Bantani presents a moderate and contextual approach to Qur’anic interpretation rooted in the principles of Ahlusunnah wal Jama‘ah. This research employs a qualitative approach with a descriptive-analytical method through a literature review of Tafsir Marah Labid and other relevant works discussing Islamic thought and modern social dynamics. The findings indicate that Imam Nawawi Al-Bantani’s ideas in Tafsir Marah Labid remain highly significant in addressing global issues such as morality, education, social justice, and the balance between scientific advancement and spiritual values. His interpretation emphasizes the importance of harmonizing Islamic law with social realities, thus providing guidance for Muslims to uphold the teachings of the Qur’an while engaging with globalization without losing their Islamic identity. Therefore, Tafsir Marah Labid by Imam Nawawi Al-Bantani serves not only as a classical intellectual legacy but also as an inspiration for building a moderate, adaptive, and civilized Islamic.